2006
DOI: 10.1007/s10198-006-0343-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the costs of emergency medical admissions to an Irish teaching hospital

Abstract: This study examined whether there is a relationship between coded diseases at the time of hospital discharge and costs of hospital re-admission. We carried out a systematic review of data relating to emergency medical patients admitted to St. James' Hospital in Dublin between 1 January 2002 and 31 October 2004. Data on discharges from hospital were analyzed as recorded in the hospital in-patient enquiry (HIPE) system. Of 15,876 episodes recorded among 11,201 patients admitted the number of re-admissions number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Persons with a psychiatric diagnosis present to the emergency department (ED) 5 times more often than persons without a psychiatric diagnosis, and these visits are associated with increased hospital costs (Brennan, Chan, Hsia, Wilson, & Castillo, 2014; Moloney, Bennett, & Silke, 2006; Williams et al, 2001). Patients requiring psychiatric care are often met with contempt by ED staff, who might deem their visit to be unnecessary or inappropriate (Sulzer, 2015; White, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Persons with a psychiatric diagnosis present to the emergency department (ED) 5 times more often than persons without a psychiatric diagnosis, and these visits are associated with increased hospital costs (Brennan, Chan, Hsia, Wilson, & Castillo, 2014; Moloney, Bennett, & Silke, 2006; Williams et al, 2001). Patients requiring psychiatric care are often met with contempt by ED staff, who might deem their visit to be unnecessary or inappropriate (Sulzer, 2015; White, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the introduction of an AMAU speeded access to an acute medical service, and reduced costs by reducing LOS 6 7. Variations between consultants’ practice in the AMAU may reflect a genuine special interest bias, or absence of definitive guidelines for the management of common acute medical conditions 9.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is recognised that an acute hospital can expect regular bed shortages for emergency department patients when hospital bed occupancy rates exceed 85%, and periodic bed crises if hospital bed occupancy rises to 90% or more 4 5. We have previously reported how the introduction of an acute medical admissions unit (AMAU) facilitated speedier access from the emergency department to the acute medical service, and reduced hospital costs by decreasing length of stay (LOS) 6 7…”
mentioning
confidence: 99%
“…In recent years, repeated emergent hospitalization for patients with acute heart failure (HF) has become a cause for significant medical and economic burden [1][2][3][4]. It is well recognized that educating patients about early signs of HF exacerbation and providing them with early medical intervention in ambulant settings are important to prevent emergent rehospitalization [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%